Surgical Time of Day Does Not Affect Outcome Following Hip Fracture Fixation - Switzer, Julie A. (SAGE Publications, 2013)
BACKGROUND: Due to the need for medical optimization and congested operating room schedules, surgical repair is often performed at night. Studies have shown that work done at night increases complications. The primary aim of our study is to compare the rates of complications and 30-day mortality between 2 surgical times of day, daytime group (DTG, 07:00-15:59) and nighttime group (NTG, 16:00-06:59). METHODS: Retrospective chart review from 2005 through 2010. SETTING: Level 1 Trauma Center. PARTICIPANTS: 1443 patients with hip fracture, age ≥50 years with isolated injury and surgical treatment of the fracture. MAIN OUTCOMES AND MEASURES: Thirty-day mortality and complications: myocardial infarction, cardiac event, stroke, central nervous system event, pneumonia, urinary tract infection, postoperative wound infection, and bleeding requiring transfusion of 3 or more red blood cell units. RESULTS: A total of 859 patients met the inclusion criteria; 668 patients in the DTG and 191 patients in the NTG. The 30-day mortality was 7.8%. The complication rate was 28%. No difference was found in 30-day mortality or complication rate based on the time of day the surgery was performed (P = 1.0 and P = .92, respectively). This remained unchanged when controlling for health status and surgical complexity. Age (odds ratio = 1.03/year), Charlson Comorbidity Index (CCI; odds ratio = 1.21), and American Society of Anesthesiologists (ASA; odds ratio = 1.85) score were predictive of adverse outcomes. CONCLUSION: Surgical time of day did not affect 30-day mortality or total number of complications. Age, ASA score, and CCI were associated with adverse outcomes.